Market Analysis of sub-6 GHz Wideband Receivers - Jan M. KELNER; Jarosław KRYGIER (Communications of International Proceedings, 2021)
This paper focuses on the market analysis of radio receivers operating in the sub-6 GHz band. This analysis was performed for the ongoing project needs related to the development of a broadband radiocommunication recorder. The designed system should operate in the 1÷6 GHz band and enable continuous recording of a signal with a bandwidth of 500 MHz for 12 hours. Due to the dedicated requirements of the customer, such devices cannot be purchased directly on the market. Thus, the broadband recorder had to be made from scratch. However, the main element of the recording system is a broadband receiver, which will ensure the reception of signals from the radio path and its smooth processing into digital form. This analysis is aimed at assessing the possibility of acquiring a commercial receiver for the developed system.
Keywords: Broadband Radio Receiver; Broadband Radiocommunication Recorder